Dietary fat and cardiovascular disease? - Merijanti, Lie T. (Faculty of Medicine, Trisakti University, 2015)
Dietary saturated fat (SF) intake has been shown to increase low density lipoprotein (LDL) cholesterol and therefore has been associated with increased risk of cardiovascular disease (CVD). This evidence coupled with inferences from epidemiologic studies and clinical trials, had led to longstanding public health recommendations for limiting SF intake as a means of preventing CVD. However the relationship between SF and CVD risk remains controversial, due at least in part to the intrinsic limitations of clinical studies that have evaluated this relationship. A recent meta analysis showed that current evidence does not clearly support cardiovascular guidelines that encourage high consumption of polyunsaturated fatty acids (PUFA) and low consumption of total SF. They found weak positive associations between circulating palmitic and stearic acids (found largely in palm oil and animal fats, respectively) and CVD, whereas circulating margaric acid (a dairy fat) significantly reduced the risk of CVD.(2,3) Saturated fat are not associated with all cause mortality, CVD, CHD, ischemic stroke or type 2 diabetes, but the evidence is heterogenous with methodological limitations.